Nghiên cứu chế tạo lớp phủ nanocompozit nhôm oxit có chứa ống nano cacbon (CNTs/Al2O3) bằng công nghệ phun phủ plasma - Hà, Phạm Thị; Tuấn, Nguyễn Văn; Lý, Phạm Thị; Quý, Lê Thu (Vietnam Journal of Chemistry, 2016)
The CNTs/Al2O3 nanocomposite coating was made by plasma spraying from nanoscale Al2O3 powder mixed with CNTs. Nanosized powders cannot be plasma sprayed owing to its tendency of clogging the plasma gun nozzle. Hence, before spraying, powder treatment is a necessary requirement. In this study, nanoscale Al2O3 powder and CNTs (2 wt.%) were combined in Polyvinylalcohol (PVA) binder solution. Spray drying method was used to produce micron-sized Al2O3 powder containing CNTs (CNTs/Al2O3 powder). The coating morphology, wear resistance, microstructure and phase composition were characterized. The study results showed that, CNTs have clustered into clumps in the CNTs/Al2O3 coating. The coating consists of a mixture α-Al2O3 and γ-Al2O3 phases. In comparison with the Al2O3 coating without CNTs, the wear resistance of the CNTs/Al2O3 coating is about 20 % higher